Pengembangan Instrumen Keterampilan Komunikasi Ilmiah dalam Pembelajaran Fisika - Susi Fenti; Siti Patonah; Harto Nuroso (Jurnal Penelitian Pembelajaran Fisika, 2017)
This aims of this research is to develop and produce assessment  scientific communication skills instruments in physics learning of X grade senior high school is valid so it can be used to measure the scientific communication skills possessed and controlled by the students.This research is development of research use 4D model. This research is done through 4 stages, which are (1) analysis stage, (2) planning stage, (3) development stage, and (4) spread stage.This instrument assessment contains a descriptiontheory,concept definition, operationaldefinition, the latice instrument assessment scientific communication skill, assessment sheets of scientific communication skill, rubric assessment,scoring, and recapitulation score of scientific communication skill than have been validated by experts and tested.From the results of expert validation obtained an average 75,55% percentage which show the criteria of scientific communication skill assessment instrument is very valid. This instrument is tried of 32 students of class X MIA 1 in SMA N 3 Demak and done by conducted by 1 physics teacher. The results of trial shown that percentage of products developed base on response obtained average percentage of 88,83% with very valid criteria. While, the result of validity analysis show that there are 4 (9,3%) item statement is not valid because rxy <0,35, whereas 39 (90,7%) Other statement items are valid with rxy> 0,35. Invalid statements include item number 24, 29, 36, and 43. In the reliability analysis obtain value result rcritic = 0,84432, while rtable = 0,35. From the analysis of the reliability values obtained rcritic > rtable it can be concluded that the assessment instruments already reliable scientific communication skills.